PERAN AKTOR DALAM MELESTARIKAN RUMAH ADAT KENEGERIAN SENTAJO KABUPATEN KUANTAN SINGINGI - Yunita Tri Sativa; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Culture is something that is very essential in the humanization process in a cultured society. In practice, every actor or stakeholder must preserve the heritage of their ancestors so that they do not disappear from the habits that have been applied. Traditional houses are one way for the Indonesian people to introduce their cultural wealth. Each region in Indonesia has a different culture, lifestyle, so that these differences create their own characteristics and privileges. The purpose of this study is to describe the role of the actor in an effort to preserve the traditional house in Sentajo Country. This study uses descriptive qualitative methods with interview and documentation techniques to obtain a real picture of how the role of actors in the effort to preserve traditional houses in Sentajo Country and the obstacles faced by actors in preserving Sentajo traditional houses. The data used are primary data obtained from research informants and supported by secondary data obtained from various government agencies and customary institutions. The results of the study indicate the role of the actor in the effort to realize the Traditional Tourism House in Kenegerian Sentajo. The efforts made are to use the theory of the government's role, namely (1) the role as a community service, (2) the role as a facilitator, (3) the role as a companion, (4) the role as a partner, (5) the role as a funder. And the obstacles faced by actors in preserving the traditional house of the Sentajo country are changes in the price of wood, the number of types of work that are not included in the old RAB, the RAB does not match the unit price, it is necessary to revise the RAB. Keywords: Role, Actor, Institution